Differential proteomics analysis of proteins from human diabetic and age-related cataractous lenses - Jing Zhu; Jun Shao; Yong Yao; Zhao Dong Chu; Qian Qian Yu; Wei Zhao; Qing Lin; Zi Yin Zhang (Journal of Research in Medical Sciences, 2013)
Backgound: To investigate the differential lens proteomics between diabetic cataract, age-related cataract, and natural subjects. Materials and Methods: Two-dimensional electrophoresis (2-DE), mass spectrometry (MS), and enzyme-linked immunosorbent assay (ELISA) were employed. Total soluble proteins in lenses of type I diabetic cataract, age-related cataract (nondiabetic) patients, and normal control were extracted and subjected to 2-DE. The differential protein spots were recovered, digested with trypsin, and further applied to MALDI-TOF-MS. ELISA analysis was used to determine the levels of differential proteins in lenses of three groups. Results: 2-DE analysis reflected that lens proteins of normal control, diabetic, and age-related cataract subjects were in the section of pH 5-9 and the relative molecular weights were 14-97 kDa, while relative molecular weight of more abundant crystallines was localized at 20-31 kDa. five differential protein spots were detected and identified using MALDI-TOF-MS, including beta-crystallin A3, alpha-crystallin B chain, chain A of crystal structure of truncated human beta-B1-crystallin, beta-crystallin B1, and an interesting unnamed protein product highly similar to alpha-crystallin B chain, respectively. ELISA analysis revealed that lenses of diabetic cataract patients should contain significantly more concentrations of beta-crystallin A3, alpha-crystallin B chain, and beta-crystallin B1 than those of age-related cataract patients and normal control. Conclusion: This study clearly reflected the differential proteins of diabetic cataract, age-related cataract lenses compared with natural subjects, and it is helpful for the further research on the principles and mechanisms of different types of cataract.